Critiquing the Regulation of Houses of Worship: An Analysis Based on Quranic Moderation - Yahya, Ahmad; Irma, Ade; Bastih, Abdul (Tasamuh: Jurnal Studi Islam, 2026)
This research aims to critically review the Joint Ministerial Regulation (PBM) No. 9 and 8 of 2006 (PBM) using the framework of religious moderation values from the Quran as the main analytical tool. Using a qualitative library research method, this study critically analyzes the text of the PBM and relevant Quranic verses. The analysis reveals that the principle of moderation in the Quran strongly emphasizes justice, tolerance, and dialogue. When applied to evaluate the PBM, two main problematic clauses were identified: (1) The quantitative requirement of 90 users and 60 local supporters, which, despite its aim to encourage dialogue, in practice often becomes a procedural obstacle that hinders minorities and is susceptible to misuse. (2) The role of the Religious Harmony Forum (FKUB), which is suboptimal due to internal and external constraints, rendering its function as a mediator and facilitator ineffective. This study concludes that although the PBM has a foundation aligned with the spirit of moderation, the implementation of its crucial articles often contradicts the essence of justice and tolerance taught by the Quran. Therefore, regulatory improvements are needed to bridge the gap between theological ideals and the reality of public policy in Indonesia.